How Is It Possible to Confront Coloniality Through Devouring? An Anthropophagic Decolonial Approach - Guimarães, Renato Silva; Ferreira, Arthur Arruda Leal (Journal of Theoretical and Philosophical Psychology, 2024)
In the late 1920s, Oswald de Andrade (1890–1954), who we will refer to as Oswald, sought to develop a theory/praxis that was initially configured as an aesthetic movement within the framework of Brazilian artistic modernism but which later became a peculiar type of thought with philosophical, epistemological, historical, cultural, political, and metaphysical (or antimetaphysical) connotations. Oswald’s intellectual production was born at the intersection of perspectives between the world wars and the postwar period. Oswald’s account of Western knowledge through his interpretation of indigenous metaphysics resulted in a provocative epistemology. In this work, we will present his artistic manifestos of the 1920s and also his academic texts of the 1940s and 1950s. This artistic and philosophical work is called Anthropophagic movement, and it is an experimental metaphysics entailing a new kind of thought and aesthetic sensibility. For that we will reaffirm his formulations by reintroducing his thoughts, aiming at creating new developments that lead to a generative discussion of his approach to a decolonial project. We show that Oswald’s approach was groundbreaking at his time, and it still is regarding certain approaches of current decolonial thought of the present.
CRIS-Team Scopus Importer:2024-10-18
Keywords: cultural anthropophagy; decoloniality; experiential metaphysics; indigenized epistemology; philosophy